2021
DOI: 10.1021/acsami.1c12166
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning Window Apertures in ZIF-8/67 Frameworks by Metal Ions and Temperature for High-Efficiency Molecular Sieving of Xylenes

Abstract: Separation of structurally similar components from their mixtures is one of the most promising applications of metal−organic frameworks (MOFs). A high efficiency of such molecular sieving requires fine tuning of the MOF structure. In this work, we investigate subtle metal-and temperature-induced changes in window dimensions of zeolitic imidazolate frameworks (ZIF-8(Zn) and ZIF-67(Co)) and apply such structural tuning for efficient separation of xylene isomers (p-, m-, and o-xylenes). The use of Co instead of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The very different pX selectivity between MAF-88 and MAF-89 highlights the critical role of pore size especially at the apertures. High pX selectivity of 81.2/98.9 and promissing pX capacitiy of 2.2/2.7 mmol g −1 were recently reported for SOD-[Zn- pores, but they need more than 8 h to reach equilibrium [38].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The very different pX selectivity between MAF-88 and MAF-89 highlights the critical role of pore size especially at the apertures. High pX selectivity of 81.2/98.9 and promissing pX capacitiy of 2.2/2.7 mmol g −1 were recently reported for SOD-[Zn- pores, but they need more than 8 h to reach equilibrium [38].…”
Section: Resultsmentioning
confidence: 95%
“…While many thermodynamic, kinetic, and even molecularsieving separation mechanisms have been reported [23][24][25][26], only ultramicropores with sizes similar to that of pX achieved high pX selectivity over 10 [2,3,21,22,27-34]. The size/shape-matched pores can achieve better guest recognition, while the ultra-small pore apertures enlarge the difference of guest adsorption/diffusion rates through the gating mechanism (transisent opening/closing of relatively small pore apertures), although these structural responses are often ignored due to the difficulty of characterization [22,23,[35][36][37][38][39]. However, such adsorbents generally possess discrete (0D) or one-dimensional (1D) pores with low porosities (void ratio < 20%) and high gating barriers (relatively rigid), giving low adsorption capacities (< 2.0 mmol g −1…”
Section: Introductionmentioning
confidence: 99%
“…High diffusion rates drastically decrease the adsorption-desorption time, which is crucial for industrial applications ( 32 ). In this regard, operation at elevated temperature is necessary to achieve fast kinetics and sufficient diffusion rate for practical separations of xylene mixtures.…”
mentioning
confidence: 99%
“…[ 27,28 ] The effective aperture of the cavity windows of ZIF‐8 has been calculated to be ≈0.7 nm. [ 29 ] However, there are several studies where ZIF‐8 has been observed to adsorb larger molecules than its pores. [ 30 ] This suggests that the adsorption occurs both on exterior surfaces of nZIF‐8 particles and on CNFs, owing to charge exchange, and at least partially inside the pores (Table S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%